2017
DOI: 10.1155/2017/8761610
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Essential Oil ofEucalyptus camaldulensisDehnh. against SelectedFusariumspp.

Abstract: The objective of this study was to evaluate the antifungal activity of essential oil (EO) of Eucalyptus camaldulensis Dehnh. against five Fusarium spp. commonly associated with maize. The essential oil had been extracted by steam distillation in a modified Clevenger-type apparatus from leaves of E. camaldulensis and their chemical composition characterized by gas chromatography mass spectrometry. Poisoned food technique was used to determine the percentage inhibition of mycelial growth, minimum inhibitory conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 21 publications
4
73
0
2
Order By: Relevance
“…Therefore, in recent years, there has been increasing interest in searching for biological antifungal agents to replace synthetic pesticides. Among natural antimicrobial products, particularly interesting are plant products such as essential oils (EOs), which are some of the most promising phytochemicals and can be used for the preservation of cereals and their products (Singh et al 2010; Boukaew et al 2017; Foltinová et al 2017; Gakuubi et al 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in recent years, there has been increasing interest in searching for biological antifungal agents to replace synthetic pesticides. Among natural antimicrobial products, particularly interesting are plant products such as essential oils (EOs), which are some of the most promising phytochemicals and can be used for the preservation of cereals and their products (Singh et al 2010; Boukaew et al 2017; Foltinová et al 2017; Gakuubi et al 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Essential oil of E. camaldulensis was shown to inhibit mycelial growth of fungi, F. oxysporum, F. verticillioides, F. solani, F. subglutinans and F. proliferatum. It was observed as effective at 7, 8 and 10 μL/mL on the 5 th day [32]. The results revealed that E. camaldulensis leaf oils provided 100% inhibition of the mycelial growth of Thanatephorus cucumeris (5 mg/mL), and Chaetomium globosum (10 mg/mL).…”
Section: The Herbicidal Effects Of Essential Oilmentioning
confidence: 93%
“…Furthermore, one of the more commonly used in antifungal bioassays is the poisoned food technique [26]. The huge number of different assays often makes it impossible to compare results between different studies.…”
Section: Methodologies Of Screeningmentioning
confidence: 99%